Pengaruh Corporate Governance dan Corporate Social Responsibility Disclosure Terhadap Tax Avoidance pada Perusahaan Tambang di Bursa Efek Indonesia Periode 2019–2021 - Wulandari, Suci; Sutardjo, Agus; Lady Silvera, Dica (Ekasakti Pareso Jurnal Akuntansi, 2024)
This study aims to analyze and determine the effect of corporate governance and corporate social responsibility disclosure on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. Data collection techniques used are websites and documentation. The type of data is quantitative data with secondary data sources. The population used in this study are mining companies listed on the Indonesia Stock Exchange for 2019–2021 with a total of 47 companies by purposive sampling, so the number of samples is 11 companies x 3 years = 33 financial reports. The data analysis method in this study uses multiple linear regression analysis, the coefficient of determination, and hypothesis testing T-test and F-test. The results of this study indicate that: 1. The proportion of independent commissioners (KIND) partially has a significant positive effect on company tax avoidance (TAX) mines listed on the Indonesia Stock Exchange (IDX). 2. Partial institutional ownership (KI) has no significant effect on the tax avoidance (TAX) of mining companies listed on the Indonesia Stock Exchange (IDX). 3. Managerial ownership (KM) partially has a significant negative effect on the tax avoidance (TAX) of mining companies listed on the Indonesia Stock Exchange (IDX). 4. The audit committee (KA) partially has a significant positive effect on the tax avoidance (TAX) of mining companies listed on the Indonesia Stock Exchange (IDX). 5. Corporate social responsibility disclosure (CSRD) partially has a significant positive effect on the tax avoidance (TAX) of mining companies listed on the Indonesia Stock Exchange (IDX). 6. The proportion of Independent Commissioners (KIND), Institutional Ownership (KI), Managerial Ownership (KM), Audit Committee (KA), and Corporate Social Responsibility Disclosure (CSRD) simultaneously have a significant positive effect on tax avoidance (TAX) of registered mining companies on the Indonesia Stock Exchange (IDX).